De leidende mens. 1 algemene benadering - Apostel, Leo 1925-1995; Lievegoed, Bernardus Cornelis Johannes; Cuvelier, F.; De Voght, Karel 1933-2018 (Leuven Acco, 1979)
Over authenticiteit, eerbied, verdraagzaamheid en wijsheid.
Keywords: #GOSA:V.Alg.M